2018
DOI: 10.4314/sajas.v48i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape pomace and vitamin E on performance, antioxidant status, immune response, gut morphology and histopathological responses in broiler chickens

Abstract: We investigated the effects of grape pomace (GP) and vitamin E on the performance, antioxidant status, immune response, gut morphology and histopathological responses in broiler chickens. Two hundred and fifty male broiler chickens (Ross 308) were allocated to five dietary treatments (50 birds/treatment) in a completely randomized design. The experimental diets were as follows: i) Control corn-soybean meal diet (C); ii) C + Vitamin E (200 mg/kg of α-tocopherol acetate); iii) The diet containing 5%GP; iv) The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 49 publications
7
53
2
1
Order By: Relevance
“…Grape seed supplementation in the diet did not significantly affect blood plasma AST and ALT levels of broilers. Similarly, Ebrahimzadeh et al (2018) GP supplementation to chicken diets did not have any significant impact on serum glucose while decreased triglycerides, LDL and increased HDL concentration of serum blood of broilers. In this study, the hypolipidemic effects of GP might not originate from their direct effect on lipid metabolism; however, it could be mediated by their effect on lowering oxidized lipid products.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Grape seed supplementation in the diet did not significantly affect blood plasma AST and ALT levels of broilers. Similarly, Ebrahimzadeh et al (2018) GP supplementation to chicken diets did not have any significant impact on serum glucose while decreased triglycerides, LDL and increased HDL concentration of serum blood of broilers. In this study, the hypolipidemic effects of GP might not originate from their direct effect on lipid metabolism; however, it could be mediated by their effect on lowering oxidized lipid products.…”
Section: Resultsmentioning
confidence: 82%
“…In this study, the hypolipidemic effects of GP might not originate from their direct effect on lipid metabolism; however, it could be mediated by their effect on lowering oxidized lipid products. This effect may be associated with an increase in the plasma HDL concentration of the respective treatment groups (Ebrahimzadeh et al, 2018). Either antioxidant parameters (GPx and TBAR) or immune responses significantly (P≤0.001) affected by treatment effect (Table 6).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Aditya et al (2018) reported that carcass traits for commercial broilers were not significantly affected by GP addition (5, 7.5 and 10 g/kg) compared with the control. Dietary grape pomace (5, 7.5 and 10%) addition had no significant effect on relative weights of carcass, abdominal fat, liver and heart for broilers (Ebrahimzadeh et al, 2018). El-Kelawy et al (2018) found that natural sources of polyphenols supplementations to broiler chickens diet increased percentage of dressing and total edible parts compared with control.…”
Section: Carcass Traits:-mentioning
confidence: 99%
“…Also, Farahat et al (2017) found that GSE can be used as an effective natural antioxidant and immune stimulating agent in broiler diets from 125 to 250 mg/kg diet. Recently, Ebrahimzadeh et al (2018) reported that dietary addition of grape pomace could increase the antioxidant and immune responses parameters of treated broilers. Regarding the blood biochemical parameters, Hajati et al (2014) indicated that addition of 450 mg GSE/kg to broiler diet decreased total cholesterols, triglycerides, LDL and vLDL.…”
Section: Hematological and Biochemical Parametersmentioning
confidence: 99%